2014
DOI: 10.1021/am504926r
|View full text |Cite
|
Sign up to set email alerts
|

Universal Electrode Interface for Electrocatalytic Oxidation of Liquid Fuels

Abstract: Electrocatalytic oxidations of liquid fuels from alcohols, carboxylic acids, and aldehydes were realized on a universal electrode interface. Such an interface was fabricated using carbon nanotubes (CNTs) as the catalyst support and palladium nanoparticles (Pd NPs) as the electrocatalysts. The Pd NPs/CNTs nanocomposite was synthesized using the ethylene glycol reduction method. It was characterized using transmission electron microscopy, energy dispersive X-ray spectroscopy, X-ray diffraction, voltammetry, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 64 publications
2
23
0
Order By: Relevance
“…The peaks in the forward scan correspond to the oxidation of alcohol on the catalyst, while those in the backward scan are due to the oxidation of intermediate products produced from the forward scan. 35 It can clearly be observed that Pt/MNCS exhibits a higher electro-catalytic activity than Pt/C for the oxidation of both methanol and ethanol. The electrochemical performance parameters of different catalysts were compared and are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 96%
“…The peaks in the forward scan correspond to the oxidation of alcohol on the catalyst, while those in the backward scan are due to the oxidation of intermediate products produced from the forward scan. 35 It can clearly be observed that Pt/MNCS exhibits a higher electro-catalytic activity than Pt/C for the oxidation of both methanol and ethanol. The electrochemical performance parameters of different catalysts were compared and are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 96%
“…For the aforementioned reactions, high‐performance electrocatalysts were reported which made use of noble metal‐based materials, for example Ir and Ru oxides in case of the OER, [10–12] and Pt, Pd and Au‐based materials for the iPOR [4,13–20] and the GOR [5,21–32] . However, in addition to their scarcity and expensiveness, their severe CO poisoning [33,34] is problematic for alcohol oxidation as for these reactions all intermediates contain CO species [5,6] .…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] For example, lactic acid finds applications in different industries such as food, cosmetics, textiles and dairy as pH regulator, preservative, antibacterial and moisturiser, [7] while glycolic acid serves as a degreasing agent and is used in skin care products. [8,9] For the aforementioned reactions, high-performance electrocatalysts were reported which made use of noble metalbased materials, for example Ir and Ru oxides in case of the OER, [10][11][12] and Pt, Pd and Au-based materials for the iPOR [4,[13][14][15][16][17][18][19][20] and the GOR. [5,[21][22][23][24][25][26][27][28][29][30][31][32] However, in addition to their scarcity and expensiveness, their severe CO poisoning [33,34] is problematic for alcohol oxidation as for these reactions all intermediates contain CO species.…”
Section: Introductionmentioning
confidence: 99%
“…The catalyst's activity and stability of alcohol oxidation in alkaline medium depend not only on the presence of metal nanoparticles but also on the properties of support material and interactions between the metal particles and support materials. Generally, conductive polymers [11]; carbon-based materials like graphene, carbon nanotubes, carbon fibers, and mesoporous carbon [12][13][14][15]; metal sulfides [16]; and zeolites [17] are used as catalyst supports for various applications.…”
Section: Introductionmentioning
confidence: 99%